2007
DOI: 10.1007/s00125-007-0657-5
|View full text |Cite
|
Sign up to set email alerts
|

Association testing of common variants in the insulin receptor substrate-1 gene (IRS1) with type 2 diabetes

Abstract: Aims/hypothesis Activation of the insulin receptor substrate-1 (IRS1) is a key initial step in the insulin signalling pathway. Despite several reports of association of the G972R polymorphism in its gene IRS1 with type 2 diabetes, we and others have not observed this association in well-powered samples. However, other nearby variants might account for the putative association signal. Subjects and methods We characterised the haplotype map of IRS1 and selected 20 markers designed to capture common variations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Participants' age range in this study (30-45 years) will allow to verify if the relationship between s-Klotho and cardiometabolic risk markers levels can also be detected in younger but not too young individuals. The age of onset of age-related cardiometabolic diseases decreases in western countries [40,41], increasing in thirties [42,43]. The onset of these disorders may occur even 9-12 years before its clinical diagnosis [44].…”
Section: Introductionmentioning
confidence: 99%
“…Participants' age range in this study (30-45 years) will allow to verify if the relationship between s-Klotho and cardiometabolic risk markers levels can also be detected in younger but not too young individuals. The age of onset of age-related cardiometabolic diseases decreases in western countries [40,41], increasing in thirties [42,43]. The onset of these disorders may occur even 9-12 years before its clinical diagnosis [44].…”
Section: Introductionmentioning
confidence: 99%
“…We also included a set of trios originating from the Botnia region of Finland. This sample, FL2, consisted of 211 probands (multiple diabetic sibs) and 370 parents [ 17 , 18 ]. All study samples are summarised in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This is because alleles at 2 different markers have different frequencies and thus not the same as in the case of an absolute LD. Because in the association analysis of marker rs1896832 only a proportion of A alleles has a different effect compared with the other G alleles (those in linkage with the C allele of marker rs956115), a larger sample of individuals as reported by others would be required to detect a significant effect of allele A (51). An independent validation would also allow a better estimation of allelic frequencies of the IRS-1 gene, which in our study showed some differences, likely attributable to the sample size, in patients with and without DM.…”
Section: Figure 3 Association Between Rs956115 Genotype Status and Mamentioning
confidence: 97%